THE EFFECT OF DEFAULT RISK AND UNEXPECTED EARNING ON CUMULATIVE ABNORMAL RETURN OF INDONESIAN REAL ESTATE COMPANIES - Kartika Dewi* , Yen Sun (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This paper examines whether Default Risk and Unexpected Earning have any effect on Cumulative Abnormal Return using the control variables of beta, growth, and size and variable interaction between Unexpected Earning with Default Risk, Beta, Growth, Size. The research sample includes 21 real estate companies listed in Indonesian Stock Exchange within the period of 2011-2016. Reverse regression method was used. The results show that Unexpected Earnings, growth and size effect have a significant effect on Cumulative Abnormal Return. All interaction variables have a significant effect on Cumulative Abnormal Return. Higher Unexpected Earning means higher profit quality and higher investors trust, which then will contribute to higher Cumulative Abnormal Return. Further, growth and size contribute to higher Cumulative Abnormal Return because the longer companies operate, the bigger their growth in terms of revenues and total assets.